Digital transformation in naval industry - Bezerra, Nelson Roberto de Albuquerque; Marchisotti, Gustavo Guimarães; Bezerra, Marlene Jesus Soares; Farias Filho, José Rodrigues de (Brazilian Journal of Operations & Production Management, 2024)
Goal: The purpose of this article is to analyze how digital transformation can contribute to increasing the sustainable competitiveness of the shipbuilding industry in a developing country like Brazil. Design / Methodology / Approach: To achieve this, a conceptual model was proposed, built from a literature review and interviews with 14 experts in the naval and offshore industry. The model was then validated through structural equation modeling, considering 326 responses from professionals in the researched sector. Results: As a result, a model was developed, suggesting that to establish a Shipyard 4.0, enhancing the sustainable competitiveness of shipbuilding, it is necessary to align corporate strategic management with sustainable management of complex projects. This alignment should focus on the qualification of specialized labor to execute the entire Smart product lifecycle, encompassing intelligent design, manufacturing, assembly, and operation, all of which are integral to a Shipyard 4.0. Limitations of the investigation: Bibliography searches on the topic were limited to thematic areas such as: digital shipyard, shipbuilding, digital transformation, intelligent manufacturing, automation, management, productivity, sustainability, people, security, labor, engineering, energy, computer science, economics, mathematics. The research aimed to provide results that characterized the application of a model that integrated digital transformation into the shipbuilding industry, in the thematic areas considered in the bibliographical research. Practical implications: It is expected that this model will be applied in a shipyard as a pilot for validation through a case study, aiming to enhance the competitiveness of companies in the sector while considering the sustainable aspects associated with such endeavors. Originality / Value: In this exploratory essay, we seek the intersection of themes such as Effective Management, Smart Manufacturing, Sustainable Project and Digital Shipyard. Brazil in 2018 had around 42 shipyards as Sinaval (2018) indicates on its website, through the map of shipyards and it is believed that the research can meet future demands of the sector. It is noted that there is no digital production line in Brazil at the end of 2018, therefore the thesis proposal is innovative.